Tolerating losses for growth: J-curves in venture capital investing - Thomas Hellmann; Alexander Montag; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2024)
Startups face a trade-off between short-term profitability versus long-term growth where investors tolerate prolonged financial losses. We present a new theory and empirical evidence about the existence and shape of so-called J-curves. The theory predicts that investors facing better exit opportunities have a higher loss tolerance, encouraging startups to pursue more ambitious growth strategies. Empirically, we examine a large Swedish dataset with detailed cash flow information. Swedish startups backed by US venture capitalists experience deeper J-curves than those backed by non-US venture capitalists. They have more successful exits, higher exit values, faster sales growth, and more follow-on funding.
Keywords: F39; G24; L26; O16; 330; Venture Capital; Loss tolerance; J-curves; Entrepreneurship; Exits